HUBUNGAN INDEKS MASSA TUBUH DENGAN MENARCHE DINI PADA SISWI KELAS IV - V DI SD NEGERI 014 SIALANG KAYU BATU KECAMATAN BUNUT KABUPATEN PELALAWAN - Siti Romlah (Jurnal Kesehatan Husada Gemilang, 2019)
Menarche or first menstruation is one of various signs in early teens and girls. Variations in the onset of menarche are influenced by various factors, one of which is weight. In this studyweight was measured using the parameters of the Body Mass Index (BMI). This is to find out the relationship between BMI and early menarche at SDN 014 Sialang Kayu Batu, Bunut District, Pelalawan Regency. This research is an analytic oSBErvational study with cross sectional study approach. The sampling technique used is total sampling. The sample size is 68 students. This research was conducted on February 22, 2019 at SDN 014 Sialang Kayu Batu, Bunut District, Pelalawan Regency. Research data obtained by questionnaire and direct measurement of weight and height. The statistical analysis used was Chi-Square. Based on Chi-Square analysis, p = 0.000 (p <0.05) showed a significant relationship. It is expected that schools, health workers are to provide information and education of health regarding early menarche to all students